The World on an equatorial projection: map of the eastern & western hermispheres. - Mitchell, S. Augustus (Samuel Augustus), 1792-1868 (S. Augustus Mitchell, 1852)
Map shows geography, cities, and place names of continents viewed in the western hemisphere, eastern hemisphere, northern hemisphere, and southern hemisphere. Includes information on "Recent Antarctic Discoveries." Relief shown by hachures, spot heights, and pictorially. No scale noted.